Small cell carcinoma of the urinary bladder - Terada, Tadashi (e-Century Publishing Corporation, 2012)
Primary small cell carcinoma of the urinary bladder is very rare; only several studies have been reported in the English literature. A 62-year-old woman was admitted to our hospital because of hematuria and dysuria. Bladder endoscopy revealed a large polypoid tumor at the bladder base. Transurethral bladder tumorectomy (TUR-BT) was performed. Many TUR-BT specimens were obtained. Histologically, the bladder tumor was pure small cell carcinoma. Immunohistochemically, the tumor cells were positive for cytokeratin (CK) AE1/3, CK CAM5.2, CK8, CK18, neurone-specific enolase, chromogranin, NCAM (CD56), synaptophysin, Ki-67 (labeling=100%), p53, KIT (CD117), and platelet-derived growth factor receptor-α (PDGFRA). The tumor cells were negative for CK5/6, CK 34BE12, CK7, CK14, CK19, CK20, p63, CD45, and TTF-1. A molecular genetic analysis using PCR-direct sequencing showed no mutations of KIT (exons 9, 11, 13 and 17) and PDGFRA (exons 12 and 18) genes. No metastases were found by various imaging techniques. The patient is now treated by cisplatin-based chemotherapy.